1993
DOI: 10.1073/pnas.90.2.542
|View full text |Cite
|
Sign up to set email alerts
|

A cyclophilin-related protein involved in the function of natural killer cells.

Abstract: Natural killer cells are non-major histocompatibility complex-restricted large granular lymphocytes that can recognize and destroy tumor cells without prior stimulation. A 150-kDa molecule on the surface of human natural killer cells was identified as a component of a putative tumorrecognition complex. We report here the isolation of cDNAs coding for the 150-kDa tumor-recognition molecule from human and mouse cDNA libraries. The amino terminus of the predicted protein contains a large hydrophobic region follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 37 publications
0
62
0
1
Order By: Relevance
“…RTN4 is a potent neurite outgrowth inhibitor and plays a role in autoimmune demyelination (29). NKTR is highly expressed on the surface of natural killer cells where it facilitates tumor cell recognition by a MHC-independent pathway (30). Expression of NKTR on the surface of glioma cells may interfere with tumor cell recognition.…”
Section: Discussionmentioning
confidence: 99%
“…RTN4 is a potent neurite outgrowth inhibitor and plays a role in autoimmune demyelination (29). NKTR is highly expressed on the surface of natural killer cells where it facilitates tumor cell recognition by a MHC-independent pathway (30). Expression of NKTR on the surface of glioma cells may interfere with tumor cell recognition.…”
Section: Discussionmentioning
confidence: 99%
“…However, several multidomain cyclophilins from different organisms have been described as well. These include Ess1/Pin1 (Hanes et al 1989;Lu et al 1996), TLP40 (Fulgosi et al 1998), hCyP33 (Mi et al 1996), CyP-13 (Zorio and Blumenthal 1999), SRcyp (Bourquin et al 1997), mocaCYP (Cavarec et al 2002), NK-TR1 (Anderson et al 1993;Rinfret et al 1994), CypRS64 and CypRS92 (Lorković et al 2004b), and Kin241p (Krzywicka et al 2001), the last eight having domains characteristic for nuclear proteins being involved in premRNA maturation. SRcyp, mocaCYP, NK-TR1, CypRS64, and CypRS92 are highly similar nuclear proteins consisting of an N-terminal PPIase domain followed by a charged domain and a C-terminal domain rich in arginine/serine (RS) dipeptides that are characteristic for splicing factors called SR proteins (Graveley 2000;Sanford et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The chemokines responsible for directing leukocyte migration during immune homeostasis and inflammation are well characterized (11,12,17,18), but there is a general lack of information regarding the role of chemokines and cell trafficking during the induction of peripheral tolerance. Previously, we showed that during the induction of tolerance to Ags injected into the eye, eyederived APCs selectively increased expression of macrophage-inflammatory protein (MIP) 3 -2 during their preferential migration to the splenic marginal zones (MZ) and that MIP-2 was responsible for recruiting NKT cells to the spleen (19).…”
mentioning
confidence: 99%